Answer:
6, 10 and 8
Explanation:
Given the recursive function an = an-1-(an-2 - 4), when a5 =-2 and a6 = 0?
a6 = a5 - (a4 - 4)
0 = -2 - (14 - 4)
2 = - (a4 - 4)
-2 = a4 - 4
a4 = -2 + 4
a4 = 2
a5 = a4 - (a3 - 4)
-2 = 2 - (a3 - 4)
-2-2 = - (a3 - 4)
-4 = -(a3 - 4)
4 = a3 - 4
a3 = 4+4
a3 = 8
Also
a4 = a3 - (a2 - 4)
2 = 8 - (a2 - 4)
2-8 = - (a2 - 4)
-6 = -(a2 - 4)
6 = a2 - 4
a2 = 6+4
a2 = 10
a3 = a2 - (a1 - 4)
8 = 10 - (a1 - 4)
8-10 = - (a1 - 4)
-2 = -(a1 - 4)
2 = a1 - 4
a1 = 2+4
a1 = 6
Hence the first 3 terms are 6, 10 and 8